!nnovation : how innovators think, act and change our world - McDonald, Kim Chandler (2013)
" Businesses looking to succeed in the digital, global economy must innovate to survive, and !nnovation highlights the pioneers who have broken the mold and led the pack in every field, from IT to food, fashion to healthcare. Innovation expert, Kim Chandler McDonald underlines the common denominators linking these highly creative people, such as their compulsion to tell their truth, unpalatable or not, their entrepreneurial instincts and their steadfast protection of their brands. This book offers: --understanding of innovation as a mindset rather than a process --insight on how to start thinking like an innovator and into how this can assist them with their own careers and goals --knowledge of how to cultivate innovation in their own team, department or business --personal accounts from international innovators !nnovation showcases interviews with over 100 people who have pushed aside the boundaries in their field, such as: Matt Flannery, CEO/Co-Founder of Kiva, the microfinancing organization working to alleviate poverty; author Seth Godin; Zappos CEO Tony Hsieh; Digital Royalty CEO Amy Jo Martin; and Chief Innovation Officer at the marketing agency MDC Partners, Faris Yakob. Chandler McDonald finds out what drives these successful innovators, what makes innovations take off and why innovation is so critical to individuals, economies and to society as a whole"--
"Any business looking to succeed in today's and tomorrow's global, digital economy must innovate. Innovation showcases the pioneers who have broken the mould and led the pack in every field from business and technology to food, fashion, culture and healthcare. It highlights the common denominators linking these highly creative people, such as their compunction to tell their truth; their entrepreneurial instincts; and their fierce protection of their 'brands'. Innovation draws on exclusive interviews with nearly 100 people who have pushed aside the boundaries in their field. It presents the inside track on who's done what, how they did it, what drives them on, and why innovation is so critical to individuals, businesses and to society as a whole. Most importantly, it will empower you and your business to be more innovative too"--
Machine generated contents note: -- Acknowledgements -- About the AuthorThe orchestration of innovation01 The me-conomics of the GDE -- Innovating from the e-conomy to the me-conomy02 The state of the nation addressed -- Taking stock of how things stack up03 Flat world navigators connecting the dots04 me-health -- Resolute and committed stakeholders at the heart of the healthcare industry05 Innovating educating 06 The power of the me-dia -- Demanding what you want delivered when, where and how you want it07 Being grounded when the sky's the limitSummary -- Biographies.
Keywords: Creative ability in business; Organizational change; Success in business; Technological innovations; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; BUSINESS & ECONOMICS / Development / Business Development; BUSINESS & ECONOMICS / Entrepreneurship; Print books